The determination of selenium and tellurium in blister copper and copper concentrates - Gray, Douglas James Skirving (Rhodes University, Faculty of Science, Department of Chemistry, 1940)
Selenium and tellurium do not occur to any great extent in Nature and they are seldom studied in any detail. However, a general understanding of their properties, both physical and chemical, is essential in an investigation of their analytical determination. A general account may be found in many of the text-books on inorganic chemistry, but the following resumè has been included in this dissertation for the sake of completeness.
Keywords: Selenium; Tellurium; Copper